Evaluation of the anti-cancer effects of a novel guanidinium-based compound, VP79s, in multiple myeloma - Amet, Rebecca (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2020)
Multiple myeloma (MM) is an incurable haematological malignancy accounting for 300-350 cancer diagnoses in Ireland each year. Mainly a disease of the elderly, MM is most prevalent in Western societies where aging populations are rising, and the likelihood of MM is increasing. MM is an extremely arduous malignancy to treat due to the marked clonal heterogeneity among patients. A better understanding of the pathophysiology of MM and advancements in the development of novel therapeutics have allowed the median survival of patients to increase from 3 to 6 years in the past decade. However, despite the effectiveness of the first-line treatments, patients invariably relapse and become refractory to treatment; therefore, novel therapeutics which target this incurable cancer are still required. The Janus kinase (JAK)/Signal transducer and activator of transcription 3 (STAT3) pathway in MM can be both constitutively active due to autonomous mutations or activated by growth and survival factors, such as interleukin-6 (IL-6), secreted by bone marrow stromal cells (BMSCs) and other cells within the bone marrow microenvironment. Increasing evidence has demonstrated that STAT3 is upregulated in MM and that STAT3 increases the expression of genes involved proliferation, angiogenesis and evasion of apoptosis. Consequently, STAT3 has emerged as a therapeutic target in various cancers including MM. In the present study, the anti-MM activity of an optimised series of novel aryl-guanidinium compounds were initially tested in a representative pair of MM cell lines, NCI-H929 and U266B1, and a lead compound, VP79s, was identified. Results with VP79s compared very favourably with those obtained with a panel of standard and emerging therapeutics used to treat MM. In contrast to these therapeutic agents, VP79s equipotently reduced the viability of a panel of myeloma cells with no resistance observed. Following on from this, VP79s was found to induce apoptosis in NCI-H929 and U266B1 cell lines in a dose- and time-dependent manner resulting in caspase 3 activation. The RAS/RAF/MEK/ERK, JAK/STAT, PI3K/AKT and NFĸB signalling pathways are known to play a key role in the pathogenesis of MM. Examination of these pathways found that VP79s rapidly inhibited both constitutively active and IL-6-induced STAT3 signalling in U266B1 and NCI-H929 cells respectively. Examination of upstream mediators of STAT3 signalling suggested that VP79s may inhibit STAT3 via inhibition of JAK2 phosphorylation and downregulation of the IL-6 receptors, CD126 and CD130. Analysis of downstream STAT3 targets demonstrated a decrease in the expression levels of anti-apoptotic Bcl-2 family member, Mcl-1; inhibitor of apoptosis protein, survivin; and the cell cycle protein, cyclin D1. In particular, treatment with VP79s resulted in a rapid time-dependent decrease in Mcl-1, a critical survival factor in MM, suggesting that VP79s may be a promising anti-MM therapeutic. Examination of the translational capacity of VP79s demonstrated that VP79s was able to enhance cell death induced by the proteasome inhibitor; bortezomib, a standard MM treatment. VP79s was also found to induce minimal cytotoxicity of peripheral blood mononuclear cells, T, B and Natural Killer cells from healthy donors at concentrations which are lethal to MM cell lines suggesting selective anti-myeloma activity. MM cells have an intricate relationship with the bone marrow microenvironment and in particular with BMSCs. MM cells rely heavily on this relationship for growth, survival and drug resistance in vivo and is mediated through the secretion of soluble factors, such as IL-6, and adhesion of MM cells to BMSCs. In contrast to bortezomib, VP79s was shown to overcome both soluble and adhesion mediated drug resistance when myeloma cells were co-cultured with the stromal cell line HS5. Finally, VP79s significantly reduced the viability of ex vivo MM patient samples in a dose-responsive manner suggesting its potential as an anti-MM therapeutic. In conclusion, a novel aryl-guanidium compound, VP79s, was identified as a lead compound capable of inhibition of the STAT3 signalling pathway and inducing potent anti-MM activity in MM cell lines and ex vivo patient samples. These data warrant further translational and pre-clinical studies into the efficacy and mechanism of action of VP79s.
APPROVED
Keywords: Multiple myeloma; Cancer; Drug discovery; JAK/STAT3; Cell signalling